Alteração de características de salinidade do solo em duas áreas de produção de melão - Oliveira, Danielle da Silva (2010)
Production of melon, which is moderately sensible to soil salinity, using water with high content of salts, inspired this work, which objectives were to quantify alterations on some soil salinity parameters during one crop cycle in two melon production areas, besides verifying the influence of such alterations on yield and quality of fruits. To accomplish this task, one cycle of commercial fertirrigated melon production was monitored in two different areas of W.G Farm, in Baraúna, RN, Brazil, where was grown the melon hybrid Iracema . Sampling was carried out in a grid scheme, with a 20 x 20 m regular spacing, which resulted in 40 plots. In each plot fruits were collected for yield determinations (number, yield and fruit mean weight of export, national and marketable fruits) and quality determinations (soluble solid content (TSS), pulp firmness and thickness). Soil characteristics determined in the beginning and in the end of crop cycle were pH, Electrical Conductivity of Soil Saturated Paste Extract (CEes), contents of Ca2+, Mg2+, K+ and Na+, Exchangeable Sodium Percentage (ESP) and the ratios Ca:Mg, Ca:K and Mg:K. Data analysis included descriptive statistics; Spearman correlation and regression analysis for identification of variability sources of yield and quality. Melon fruit yield and quality had higher influence of initial values of soil salinity parameters than of final values. Soil Mg2+ contents and CEes did not showed increase during melon cycle in both areas. Ca2+ content increased only at Bismarck area, where its final values showed positive effects on fruit pulp firmness and thickness. Ca2+ to Mg2+ ratio of Bismarck area increased 23,7 % and its final values showed positive effect on number and yield of export type and marketable fruits. Na+ contents and ESP on both areas showed increase around four times, from beginning to cycle end, but only final values of Sumidouro area showed positive effects: Na+ benefited number and yield of export type and marketable fruits, and ESP benefited yield of the same types. Increase in soil pH was around 5% on both areas, but only at Sumidouro the final values showed negative effects on mean weight of export type and marketable fruits, and on TSS.